TEXTUAL METAFUNCTION ANALYSIS ABOUT EDUCATION NEWS TEXT ON SELECTED NATIONAL ONLINE NEWSPAPERS - Shela Noviriantika Hidayah; Marwito Wihadi; Wulan Rahmatunisa (Journey: Journal of English Language and Pedagogy, 2023)
The textual meta function is about the verbal world, especially the flow of information in a text, and is concerned with clauses as messages. In each meta function an analysis of a clause gives a different kind of structure composed from a different set of elements. The aim of this study was to analyze and identify the functions took from three different online newspapers, Jakarta Post, Jakarta Globe, and Tempo, with the context of educational news on the topic, "Merdeka Belajar Curriculum". This study used a qualitative approach as its methodology. The data was taken from the websites of Jakarta Post, Jakarta Globe, and Tempo. A functional English grammar was employed to analyze the data. Based on the study's findings, it identified three themes present in the Jakarta Post, Jakarta Globe, and Tempo: topical, interpersonal, and textual. Topical theme consisted of 43.5% of the article is unmarked theme and 16.5% marked theme. Interpersonal theme consisted of 3% of the article is modal adjunct, 4% is vocatives, and 6.5% is finite. Textual theme consisted of 2% of the article is conjunctive adjunct and 24.5% is conjunctions. The result is that in online newspapers related to education, topical themes are more prevalent, whereas interpersonal themes are less common. The function of Theme-Rheme used on educational news has a different definition for each type. In the findings, topical themes are more prevalent in the news. The topical theme used a simple structure so the article can be understood. However, the percentage of each type is different between the three newspapers, the effectiveness of each media in conveying information based on its advantages and disadvantages is constant